2020
DOI: 10.1007/s42452-020-2179-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced graphene oxide amount on the tribological properties of UHMWPE biocomposites under water-lubricated conditions

Abstract: Ultra-high molecular weight polyethylene (UHMWPE) has been broadly utilized in hip and knee artificial implant due to its low friction coefficient, high wear resistance and good biocompatibility. However, some disadvantage properties such as low young's modulus and low load bearing, anti-fatigue capacity limit application areas and wear debris of UHMWPE components cause implant failure. For this reason, reduced graphene oxide (RGO) filler was produced by green synthesis with vitamin C and the influences of RGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Green dots represented the oxygen elements in the EDS maps. The dispersion of oxygen was very important because only RGOC had oxygen containing functional groups in the matrix 19 . The results obtained from the EDS analysis were compatible with XRD results.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Green dots represented the oxygen elements in the EDS maps. The dispersion of oxygen was very important because only RGOC had oxygen containing functional groups in the matrix 19 . The results obtained from the EDS analysis were compatible with XRD results.…”
Section: Resultssupporting
confidence: 80%
“…The FE‐SEM images of wear tracks for the unfilled UHMWPE and all biocomposites shown in Figure 10. It could be seen that the worn surface of unfilled UHMWPE were thin grooves in the low‐magnified image but the cracked surface layer of the polymer showed that the dominant mechanism was fatigue wear in the high‐magnified image 19 . The low‐magnified image of UHMWPE/RGOC‐0.1 biocomposite showed relatively flat surface but fatigue wear tracks were seen in the high‐magnified image.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of -BM composites, the behaviour is similar above 0.5 wt% GNP content, the difference being that below this critical concentration, there is a relative maximum in hardness at around 5.2 HV, which corresponds to 25% increase with respect to the thermoformed samples containing PE alone. This effect of GNPs on hardness is very high compared to other PE matrix composites reinforced with GO (Colak et al, 2020;Pang et al, 2018;Vadivel et al, 2018), RGO (Colak et al, 2020) J o u r n a l P r e -p r o o f and the same filler GNPs (Aliyu et al, 2019). In general, this effect is explained by an improvement in mechanical response due to load transfer through the filler sheets.…”
Section: Microhardnessmentioning
confidence: 86%
“…This approach was seen to be promising due to the efficient dispersion of GO sheets into the UHMWPE matrix, which will lead to increased wear resistance. Colak et al [27] developed RGO by green synthesis with vitamin C. The effect of RGO filler material on tribological performances under distilled water lubrication. Wear resistance property is magnified and composite with 0.7 wt% (RGO) optimum properties.…”
Section: Uhmwpe /Graphene Bio-nanocompositementioning
confidence: 99%